Which of the five classical ballet positionsis the most demanding for the dancer`s body? An electromyography-based studyto determine muscular activity - Gorwa, J.; Kabacinski, J.; Murawa, M.; Fryzowicz, A. (Acta of Bioengineering and Biomechanics, 2020)
Purpose: The study aimed to determine which of the five classical ballet positions is the most demanding regarding muscular ac-tivity, values of external rotation in the hip joints, angular values of foot progression as well as the inclination (tilt) of the pelvis inthe sagittal plane. Methods: In this crosssectional study, 14 female pre-professional ballet dancers (aged 11-16) participated. Participants were tasked with the sequential adoption of five classical ballet positions (CP1-CP5). The electromyographic activity of the muscles of the trunk and the lower limb was recorded with surface electrodes. Kinematic data including hip and knee external rotation, foot progression angle and pelvic tilt were collected using a motion capture system. Results: Symmetric positions CP1 and CP2 were not as demanding as asymmetric CP3-CP5. Higher values of hip and foot external rotation without greater muscular effort in CP2 than CP1 was noticed. Considering asymmetric positions, CP3 did not trigger a greater activity of hip or foot muscular groups than CP4 and CP5. CP4 was characterised by the greatest pelvic anterior tilt and the lowest activity of GM in the forward lower limb.In CP5, forward lower limb entailed a higher activity of muscles supporting the foot than in the remaining positions. Conclusion: Interms of biomechanics, the most demanding classical ballet position in pre-professional dancers is CP4, followed by CP5, CP3, CP1and CP2. This finding can be applied in educational methodology of dancers, figure skaters, synchronized swimmers, acrobatic gym-nasts, rhythmic gymnasts or cheerleaders.